Formulating Business Strategy in Optimum Prime Coffee Shop - Novriady, Anantadya; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2015)
Abstract.Optimum Prime is a coffee company based in Aceh, Indonesia. At the beginning, Optimum Prime’s core business is selling coffee beans. Though, over time, the OP business grew significantly. And in February 2013, Optimum Prime opened its first coffee shop in Bireun, Aceh. Coffee products sold by Optimum Prime are different from other competitors. OP grows their own coffee and their coffee is digestion friendly. In the early coffee shop established, the strategy used was to take the employee market, because of its location that close to the OP office and bank. With this growth, OP intends to open a coffee shop in Senopati, Jakarta. The competition Area between Aceh and Jakarta are very different. So, OP needs the right strategy to get into the market in Jakarta. Strategic formulation process is done through the three stages of analysis, the input phase, analysis, and decision stages. The final stage is a case analysis to formulate a decision to be taken. The decision was based on justification pedestal made qualitatively and quantitative, structured or unstructured, so that a decision can be taken significant with existing conditions.In order to start the strategic formulation process, business exploration have to be done by defining internal and external evaluation. The tools to defining internal evaluation are business model canvas and value chain analysis. PEST analysis, Porter’s five forces and competitor analysis is needed to define external evaluation. SWOT analysis is determined from internal and external analysis. Matrix IE obtained from weighted axis in EFAS and IFAS. Strategy derived from Matrix IE will be included in QSPM to be valued which strategy has the highest score. Then the highest score from QSPM will be applied to the company. So, the right strategy for OP to penetrate Senopati market is Porter’s Generic Market Penetration because OP intend to enter existing market with existing product and Frontal Attack Strategy, where OP plan their development in silent and attack with quick pace.Based on the result from the research, market penetration which could be used by the company in order to succeed in enter Senopati market with build their brand to create brand equity, do marketing research, and frontal attack the competitor.Keyword: strategic business, quantitative strategic planning matrix, Optimum Prime, formulating business strategy, Coffee Shop.